Appropriate time interval to update ambiguous genetic diagnosis in inherited arrhythmogenic syndromes - Estefanía Martínez-Barrios; Andrea Greco; Sergi Cesar; Carles Díez-López; José Cruzalegui; Nuria Díez-Escuté; Patricia Cerralbo; Fredy Chipa; Irene Zschaeck; Simone Grassi; Antonio Oliva; Norma Balderrábano; et al. (iScience)
Summary: Genetic analysis identified the cause of the disease in inherited arrhythmogenic syndromes. A clinically actionable genetic diagnosis requires an accurate interpretation following the current guidelines. Practically half of the genetic diagnoses remain inconclusive due to the identification of variants of uncertain significance. An update can help shed light on uncertain results. No specific time frame has been set for updating an ambiguous diagnosis. We carried out an analysis of the available reclassification/reinterpretation data concerning genetic diagnosis in inherited arrhythmogenic syndromes. We aim to determine an appropriate interval for updating a conclusive classification. Genetic diagnoses achieved without following current guidelines should be updated immediately. An ambiguous result obtained following the current guidelines should be updated no more than 5 years after the first analysis. There are still questions to be resolved regarding the legal responsibility or who should assume the economic cost of updating a genetic diagnosis.